Investigating the Genetic Causes of Sudden Unexpected Death in Children Through Targeted Next-Generation Sequencing Analysis. (August 2017) - Dewar, Laura J.; Alcaide, Miguel; Fornika, Daniel; D'Amato, Luisa; Shafaatalab, Sanam; Stevens, Charles M.; Balachandra, Thambirajah; Phillips, Susan M.; Sanatani, Shubhayan; Morin, Ryan D.; Tibbits, Glen F.
Abstract : Background—: Inherited arrhythmia syndromes are responsible for a significant portion of autopsy-negative sudden unexpected death (SUD) cases, but molecular autopsy used to identify potentially causal variants is not routinely included in SUD investigations. We collaborated with a medical examiner's office to assist in finding a diagnosis for their autopsy-negative child SUD cases. Methods and Results—: 191 child SUD cases (<5 years of age) were selected for analyses. Our next generation sequencing panel incorporated 38 inherited arrhythmia syndrome candidate genes and another 33 genes not previously investigated for variants that may underlie SUDY pathophysiology. Overall, we identified 11 potentially causal disease-associated variants in 12 cases, for an overall yield of 6.3%. We also identified 31 variants of uncertain significance in 36 cases and 16 novel variants predicted to be pathogenic in silico in 15 cases. The disease-associated variants were reported to the medical examiner to notify surviving relatives and recommend clinical assessment. Conclusions—: We have identified variants that may assist in the diagnosis of at least 6.3% of autopsy-negative child SUD cases and reduce risk of future SUD in surviving relatives. We recommend a cautious approach to variant interpretation. We also suggest inclusion of cardiomyopathy genes as well as other candidate SUD genes in molecular autopsy analyses. Abstract : Supplemental Digital Content is available in the text.